Analysis of the Meaning of Da'wah in Nussa and Rara Animated Films - Irmawati, Irmawati (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2023)
The rise of uneducated cartoon series that can be easily accessed on social media makes parents and the public nervous, which is the basis for this research. The purpose of this research is to find out the most powerful meaning of da'wah in the films Nusa and Rara. This research uses a quantitative method that provides accuracy and looks at the meaning of da'wah including the points of aqidah, sharia, and morals. From the results of the research carried out, the essential results show the meaning of da'wah in the animated film Nusa and Rara. The type of meaning of the largest da'wah is morals with 43% points, sharia da'wah with 30% points, and the value of aqidah da'wah with 27% points [Maraknya serial kartun yang kurang mendidik yang dapat mudah diakses di media sosial membuat resah para orangtua dan masyarakat menjadi dasar dilakukan riset ini. Tujuan riset ini adalah untuk mengetahui makna dakwah yang paling kuat didalam flim Nusa dan Rara. Riset ini memakai metode kuantitatif yang menyajikan akurasi serta mencermati makna dakwah meliputi point akidah, syariah, serta akhlak. Dari hasil riset yang dilakukan mendapatkan hasil yang esensial memperlihatan makna dakwah pada flim animasi Nussa dan Rara. Jenis makna dakwah terbesar akhlak dengan point 43 %, dakwah syariah dengan point 30%, serta nilai dakwah akidah dengan point 27%.